Hubungan Stadium dengan Kadar Hemoglobin pada Perempuan Penderita Kanker di Poliklinik Rumah Sakit Umum Pusat H.Adam Malik Tahun 2023 - Elvipson Sinaga; Linawati Togatorop; Marta Imelda BR. Sianturi (Pusat riset dan Inovasi Nasional, 2025)
Anemia is a common complication in cancer patients, especially in advanced stages, which affects quality of life and response to therapy. This study aims to analyze the relationship between cancer stage and hemoglobin (Hb) levels in female patients undergoing chemotherapy. This quantitative study used a cross-sectional design and involved 54 female cancer patients at the H. Adam Malik General Hospital Polyclinic, Medan. The sampling technique used convenience sampling. Data were analyzed using the Spearman's rho test to determine the relationship between cancer stage and Hb levels. The majority of respondents were in stage 3 (48.1%) and stage 4 (37.0%), with 63% experiencing moderate anemia (Hb 8–10 g/dL). The results of the Spearman test showed a significant positive correlation between cancer stage and Hb levels (r = 0.683; p = 0.000), indicating that the more advanced the cancer stage, the lower the hemoglobin levels tend to be. It was concluded that there was a significant relationship between cancer stage and hemoglobin levels in female patients. These results emphasize the importance of monitoring Hb levels in clinical management and nursing care of cancer patients, especially in advanced stages.